2020
DOI: 10.1039/c9ra09903d
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and photocatalytic oxidation of diphenyl sulphide to diphenyl sulfoxide over titanium dioxide doped with vanadium, zinc, and tin

Abstract: Phase transitions of rutile and anatase were directed by V, Zn and Sn admixtures. Rutile containing catalysts were more active in Ph2S oxidation than pure anatase samples. Efficiency of Ph2S oxidation was significantly improved under UV radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In this system, even when selectivity is high, the concentration of the nal product is rather low. However, we showed recently that hydrogen peroxide is a crucial oxidation agent in the photocatalytic oxidation of Ph 2 S. 26 No Ph 2 S conversion aer 3 hours of the reaction in both catalytic and photocatalytic tests conducted in the absence of H 2 O 2 over bare and doped TiO 2 materials (concentrations of Ph 2 S oxidation products below the detection limit) was observed. Nevertheless, in the presence of hydrogen peroxide, the reaction can occur at P25 (anatase and rutile mixture) both on the catalytic and photocatalytic way, with signicantly higher conversion of Ph 2 S under irradiation compared to the dark process.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In this system, even when selectivity is high, the concentration of the nal product is rather low. However, we showed recently that hydrogen peroxide is a crucial oxidation agent in the photocatalytic oxidation of Ph 2 S. 26 No Ph 2 S conversion aer 3 hours of the reaction in both catalytic and photocatalytic tests conducted in the absence of H 2 O 2 over bare and doped TiO 2 materials (concentrations of Ph 2 S oxidation products below the detection limit) was observed. Nevertheless, in the presence of hydrogen peroxide, the reaction can occur at P25 (anatase and rutile mixture) both on the catalytic and photocatalytic way, with signicantly higher conversion of Ph 2 S under irradiation compared to the dark process.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, we described that the addition of tert-butyl alcohol (hydroxyl radical scavenger) signicantly diminishes the Ph 2 S conversion. 26 Furthermore, isotopic oxygen (H 2 18 O) experiments, reported by Li et al revealed that the oxygen atoms of sulfoxide (obtained photocatalytically from phenyl sulphide in water containing mixture, in the absence of H 2 O 2 ) originated mainly from water. 51 We concluded that hydroxyl radicals play a signicant role in the rst step of diphenyl sulphide oxidation, yielding Ph 2 SO.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] Moreover, the titanium dioxide doped with vanadium(V‐TiO 2 ) showed high activity in the photocatalytic oxidation of sulfide to sulfoxide under UV irradiation. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Their importance is based on the application in pharmaceutical industries and preparing a scaffold for aryl suldes as intermediates in synthetic organic chemistry. 33,34 Although the sulde and disulde oxidation reactions have been studied extensively, [35][36][37][38][39][40][41][42][43][44] it is necessary to introduce procedures that are more simple, efficient and selective. Herein, a magnetically separable heterogeneous catalyst was fabricated by anchoring a Cu complex supported on functionalized CoFe 2 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%